Working hard or working right? Role ambiguity, hustle culture, and quiet quitting - Ary Priambodo; Okta Prihatma Bayu Putra; Muhammad Fauzi Rahman (Priviet Social Sciences Journal, 2026)
The growing normalization of hustle culture in urban workplaces raises critical concerns regarding sustainable employee engagement and the realization of decent work. In Jakarta, Indonesia’s economic center, structural role ambiguity may interact with performance-driven norms to generate concealed withdrawal behavior. This study examined the integrated relationships among role ambiguity, hustle culture, and quiet quitting among employees working in Jakarta. A quantitative cross-sectional survey design was used. Data were collected in the second semester of 2025 using an online self-administered questionnaire. Using a non-probability sampling approach, 171 eligible employees working in Jakarta were included in the study. All constructs were measured using a five-point Likert scale. Data were analyzed using a two-stage approach: Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to assess measurement and structural models, followed by regression-based bootstrapped mediation analysis in Python (5.000 resamples) to test robustness. The findings demonstrate that role ambiguity was positively associated with quiet quitting and was also positively associated with hustle culture, which partially mediates this relationship. These findings underscore the importance of role clarity and sustainable work norms in promoting decent employment in urban areas.